Screening of Bioactive Compounds of Spirulina platensis as Potential Antioxidants: An In-silico Approach - Himawan Prasetiyo; Fitri Novita Nanda; Mad Rudi; Nurul Azila Razak (Program Studi Kimia Universitas Negeri Jakarta, 2025)
Oxidative stress is a significant trigger of degenerative diseases, caused by an imbalance between free radicals and the body's antioxidant defenses. This study aims to identify bioactive compounds from Spirulina platensis and to evaluate their antioxidant potential using an in-silico approach. Candidate screening was conducted using Gas Chromatography-Mass Spectrometry (GC-MS) analysis, antioxidant activity prediction, pharmacokinetic evaluation (Lipinski's Rule of Five), and ligand–receptor interaction analysis (molecular docking). GC-MS analysis identified 30 bioactive compounds across various classes, including hydrocarbons, alcohols, phenols, aldehydes, and steroids. Activity prediction showed that all compounds exhibited antioxidant potential with Pa > 0.7 and Pi > 0.3, meeting both Lipinski's criteria and drug-likeness requirements. Among them, phytol and ethyl iso-allochol were demonstrated binding energies (∆G) of –5.0 and –7.3 kcal/mol, respectively, which were lower than the natural ligand 3-[(1R)-1-(2,6-dichloro-3-fluorophenyl) ethoxy]-5-(1-piperidin-4-yl-1H-pyrazol-4-yl) pyridin-2-amine with –8.3 kcal/mol, suggesting their potential as free radical inhibitors. The microalga S. platensis thus contains antioxidant-active compounds with promising potential for further development. However, additional evaluations through active compound isolation as well as in vitro and in vivo studies are required.